Dubious battle in California Dubious battle in California - John Steinbeck (Ilha do Desterro, 2008)
In sixty years a complete revolution has taken place in California agriculture. Once its principal products were hay and cattle. Today fruits and vegetables are its most profitable crops. With the change in the nature of farming there has come a parallel change in the nature and amount of the labor necessary to carry it on. Truck gardens, while they give a heavy yield per acre, require much more labor and equipment than the raising of hay and livestock. At
the same time these crops are seasonal, which means that they are largely handled by migratory workers. Along with the intensification of farming made necessary by truck gardening has come another important development. In sixty years a complete revolution has taken place in California agriculture. Once its principal products were hay and cattle. Today fruits and vegetables are its most profitable crops. With the change in the nature of farming there has come a parallel change in the nature and amount of the labor necessary to carry it on. Truck gardens, while they give a heavy yield per acre, require much more labor and equipment than the raising of hay and livestock. At
the same time these crops are seasonal, which means that they are largely handled by migratory workers. Along with the intensification of farming made necessary by truck gardening has come another important development.